Detection of SCCmec Gene in Methicillin - Staphylococcal Aureus - Mahdi, Dunya Talib; Isa, Jawad Kadhim (American Journal of Biology and Natural Sciences, 2024)
Objective: to detect SCCmec types I to III in Hospital-associated (HA) Methicillin-resistant Staphylococcus aureus (MRSA). Method: a total of one hundred seventy-two (N = 172) samples from different clinical cases and Health Care Workers: skin infection 46 (26.7%), surgical wounds 35(20.3%), pneumonia 27 (15.6%), septicemia 22 (12.7%), urinary tract infections 17 (9.8%) and Health Care Workers 25 (14.5%). This study was conducted at the General Hospital of Wasit during the period from December 2023 to May 2024. A combination of biochemical testing, microscopic analysis, culture, and the APIstaph system’s identification kits allowed for the confirmation of these isolates. Results: showed 34(44.15 %) of isolated S. aureus were MRSA including: in Surgical wounds 8/27 (29.6%) followed by skin infections 7/27 (25.9 %) from patients most of them were already on an antibiotic, septicemia was 6/27 (22.2%), samples of Urinary tract infection 4/27 (14.8%) while, in pneumonia, cases were 2/27 (7.4 %). The prevalence of MRSA among Health Care Workers is the highest rate were in Lab technicians at 4/7 (57.1%) followed by Nears staff at 2/7 (28.7 %) and Doctors were 1/7 (14.2 %). regarding the molecular identification of MRSA, the results showed that mecA and Insertion sequence (IS431) exist in every instance at a rate of 100% (34/34), (IS127) were 100 %, (34/34). The other genes were genes of ccrC 20/34(57.14 %) and ccrA2-B gene 6/34 (17.64 %). Conclusion: the study highlights the complexity of MRSA’s resistance mechanisms. These insights are pivotal for guiding effective treatment protocols and developing robust diagnostic tools to manage and control MRSA infections more efficiently.